Knowledge sharing memediasi pengaruh organisational justice terhadap employee innovative work behaviour - Berliana, Maghfirotus; Nugrohoseno, Dwiarko (Universitas Negeri Surabaya, 2025)
This study aims to analyse the effect of organisational justice on employee innovative work behaviour with knowledge sharing as a mediating variable. Data were collected through questionnaires distributed to employees and analysed using the Partial Least Square (PLS) method. The results showed that organisational justice has a significant positive effect on employee innovative work behaviour. In addition, organisational justice also has a significant positive effect on knowledge sharing, and knowledge sharing has a significant positive effect on employee innovative work behaviour. Knowledge sharing can mediate the effect of organisational justice on employee innovative work behaviour. These findings highlight the importance of organisational justice in fostering a culture of innovation, suggesting that fair treatment within the workplace can enhance employees' willingness to engage in knowledge sharing and innovative work behaviour. Additionally, organisations should prioritize strategies that encourage knowledge sharing, as it serves as a crucial mediating factor in strengthening the link between organisational justice and employee innovation.